(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2023)
Students in the Principles of Biology I course use a lot of course time preparing solutions each week in their course based research experience. This experiment was designed to determine the degradation rates of prepared solutions of various plant-based foods (i.e., Napa cabbage, rice, peanuts, and apple) under refrigeration as a means of reducing the amount of time for solution preparation. Scaling from the original lab procedures, approximately sixty milliliters of filtrate were prepared from the listed foods and testing was conducted on a thrice-weekly schedule. The concentration of proteins and carbohydrates were measured using the Bradford’s assay and Benedict’s test, respectively. The data revealed a noticeable trend in degradation in protein for all the samples. The rice sample proved to be an outlier with a marked increase in reducing sugars, while the other samples gradually decreased.